2019
DOI: 10.1016/s2215-0366(19)30162-2
|View full text |Cite
|
Sign up to set email alerts
|

Equity effects of parenting interventions for child conduct problems: a pan-European individual participant data meta-analysis

Abstract: Background Childhood conduct problems are a costly public health problem and are five times more common in socially disadvantaged groups than they are in advantaged groups. Untreated, conduct problems have a poor prognosis, with increasing gaps between socioeconomic groups, and high rates of subsequent criminality. Incredible Years is a high quality parenting programme for reducing conduct problems and is widely disseminated in Europe. Many trials have shown Incredible Years to be effective but the potential e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 43 publications
1
66
0
Order By: Relevance
“…This is echoed in the findings of other meta‐analyses, which also find no evidence pointing to a need for greater specificity of interventions, for example, for different cultural groups. Thus, recent work has found similar effect sizes across disparate countries and cultures (Gardner, Knerr, & Montgomery, ; Leijten et al., ), and, in IPD meta‐analysis, across ethnic and social groups (Gardner et al., ). Finally, although our findings pertain only to parenting interventions, potentially they have wider implications for early intervention policy.…”
Section: Discussionmentioning
confidence: 81%
“…This is echoed in the findings of other meta‐analyses, which also find no evidence pointing to a need for greater specificity of interventions, for example, for different cultural groups. Thus, recent work has found similar effect sizes across disparate countries and cultures (Gardner, Knerr, & Montgomery, ; Leijten et al., ), and, in IPD meta‐analysis, across ethnic and social groups (Gardner et al., ). Finally, although our findings pertain only to parenting interventions, potentially they have wider implications for early intervention policy.…”
Section: Discussionmentioning
confidence: 81%
“…The IY parenting programs have shown effect sizes ranging from d = 0.13 for preventive studies to d = 0.50 for treatment studies on parent-reported child conduct problems in a meta-analysis (34) and an overall effects size of d = 0.35 for parent-reported conduct problems in a meta-analysis using individual participant data pooled from 14 European IY trials (32). The effectiveness of the IY intervention is retained when transported to other countries (35) and is consistent across socioeconomic and ethnic background (36)(37)(38). The IY Toddler BASIC program for children 1-3 years old has shown positive results (39)(40)(41)(42), however, we know less about the effectiveness of IY programs for the youngest children (43).…”
Section: Introductionmentioning
confidence: 99%
“…A recent individual participant data meta-analysis of parenting programme effectiveness in HICs found no differential effects by family socioeconomic status. 18 The Skilful Parenting and Agribusiness Child Abuse Prevention Study aimed to investigate the inter-relationship between economic strengthening programmes and parent management training in reducing child maltreatment. This is of particular importance given the need for combined interventions that address multiple Sustainable Development Goals (SDGs) across economic, social and environmental domains.…”
Section: Economic Strengthening Programmesmentioning
confidence: 99%
“…A recent individual participant data meta-analysis of parenting programme effectiveness in HICs found no differential effects by family socioeconomic status. 18 …”
Section: Introductionmentioning
confidence: 99%